I-Pos Information System Security Audit Using Framework Control Objectives for Information and Related Technologies 2019 And Information Technology Infrastructure Library 4 - Titan Parama Yoga; Chairul Habibi; Nizar Hizbi Abdul Aziz (LPPM STMIK Mardira Indonesia, 2023)
Information system security is used to protect against cyber attack crimes. Generally, cyber attacks occur because someone wants to intervene in a system to find out the confidentiality and availability of information. PT. Pos Indonesia is a company under the auspices of SOEs engaged in distributing letters and packages. Both domestic package distribution and overseas package distribution. To facilitate the delivery of packages, PT Pos Indonesia developed an information system called I-POS. Based on the results of the researchers' analysis, the I-POS information system is an information system that aims at mail and package delivery transactions, so using the I-POS information system can facilitate the process of delivery transactions, as well as provide accurate, timely, and relevant information. The purpose of this study is to determine the level of maturity of information system security in the field of I-POS information systems at PT. Pos Indonesia, Analyzing the findings and gaps of the level of maturity of the information system security. Based on the results of research that has been conducted through questionnaires using the COBIT 2019 framework with APO13 and DSS05 domains, it was found that the Existing Capability obtained was at level 2 while the expected Capability Level was at level 5 so the Capability Gap produced in these conditions was 3 levels